Antarctica Legislation, 1960 : hearings before the United States House Committee on Interior and Insular Affairs, Subcommittee on Territorial and Insular Affairs, Eighty-Sixth Congress, second session, on June 13, 14, 1960. - United States. Congress. House. Committee on Interior and Insular Affairs. Subcommittee on Territorial and Insular Affairs. (Washington : U.S. G.P.O., 1960)
Considers (86) H.R. 5222, (86) H.R. 8481, (86) H.R. 8376, (86) H.R. 8421, (86) H.R. 8480. Committee Serial No. 27. Considers H.R. 5222 and two identical bills, to provide support for research, other activities related to Antarctica, and two related bills proposing DOD as the executive agency responsible for supervising Antarctic affairs. Record is based on bibliographic data in CIS US Congressional Committee Hearings Index. Reuse except for individual research requires license from Congressional Information Service, Inc. Indexed in CIS US Congressional Committee Hearings Index Part VII Considers (86) H.R. 5222, (86) H.R. 8481, (86) H.R. 8376, (86) H.R. 8421, (86) H.R. 8480. Committee Serial No. 27. Considers H.R. 5222 and two identical bills, to provide support for research, other activities related to Antarctica, and two related bills proposing DOD as the executive agency responsible for supervising Antarctic affairs. Mode of access: Internet.